Caravana transformării la Biblioteca Municipală „B.P. Hasdeu”: de la probleme la soluții - HARJEVSCHI, Mariana (BIBLIOPOLIS, 2025)
The article highlights the experience of the Transformation Caravan, organized under the aegis of the B.P. Hasdeu Municipal Library, aimed at addressing the institution’s major challenges and identifying innovative solutions. The initiative involved an extensive consultation process, carried out through 14 meetings held between April and November 2024, covering 21 topics. These were coordinated by the senior management team and took place across the library’s branches. The areas addressed included digital organization and functionality, internal administration and data collection, collection management, service coordination, user interaction, promotion, performance, and evaluation.